Case report: Anterior mediastinal mass in a patient with pleural effusion and dyspnea - Gu, Lin; Xin, Gaojie; Qu, Yue; Wang, Kai; Jiang, Ke; Xing, Shijie; Huang, Ai (Frontiers in Surgery, 2023)
Background Compound lymphoma (CL) is an uncommon type of lymphoid malignancy, and those consisting of concurrent B- and T-cell tumors are relatively rare. Case Summary A 41-year-old man was presented with a 1-month history of progressively worsening cough, chest tightness, and dyspnea after exercise, which could be relieved following rest. Contrast-enhanced computed tomography (CT) scan demonstrated a 7.4 x 4.9 cm2 heterogeneous mass in the anterior mediastinum, where a large area of cystic liquid existed, and multiple enlarged lymph nodes in the mediastinum. Since the biopsy failed to yield an exact diagnosis and there was no sign of metastasis, the tumor was surgically resectioned. Surgical findings included obscure boundaries and consistent tumor stiffness with pericardial and pleural invasion. Further pathological examination combined with immunophenotype and gene rearrangement test found the mass composite of angioimmunoblastic T cell lymphoma (AITL) and B cells lymphoma. The patient recovered well after R0 resection and received chemotherapy with four cycles of CHOP combined with Chidamide two weeks after surgery. The patient has had a complete response (CR) for over 60 months. Conclusion In conclusion, we reported a composite lymphoma of AITL combined with B-cell lymphomas. Our experience provides the first successful attempt to treat this rare disease with combined surgery and chemotherapy.